Well-posedness of boundary-value problems for multidimensional hyperbolic systems - Kmit, I. Ya.; Ptashnik, B. I. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
By the method of characteristics, we investigate the well-posedness of local (the Cauchy problem, mixed problems) and nonlocal (with nonseparable and integral boundary conditions) problems for some multidimensional almost linear first-order hyperbolic systems. Reducing these problems to the systems of integral operator equations, we prove the existence and uniqueness of classical solutions.